Economics in the Development and Development of Islamic Society - Rambe, Riswan; Zahra, Ilya; Nadia, Nadia (ALSYS, 2025)
This research aims to analyze the role of the Islamic economic system in community empowerment and strengthening the economic independence of the people through the use of instruments such as zakat, infaq, sedekah, productive waqf, and Islamic microfinance institutions. Researchers use a descriptive qualitative approach with data collection techniques in the form of observation, in-depth interviews with Islamic economic actors and community leaders, and documentation studies. The research results indicate that Islamic economics not only contributes to the material aspect but also functions as a mechanism for fostering the social, spiritual, and cultural development of the community. Empowerment based on zakat and productive waqf, as well as Islamic financing through Baitul Maal wat Tamwil (BMT) and Islamic cooperatives, has proven effective in improving the standard of living of people experiencing poverty, creating jobs, and strengthening social solidarity. However, the implementation of Islamic economics at the grassroots level still faces various challenges, such as low literacy of Islamic economics, limitations in the management of waqf assets, and suboptimal synergy between Islamic institutions. Therefore, it is necessary to strengthen institutions, support regulations, and integrate Islamic economics into development policies both at the local and national levels. Thus, Islamic economics can be an alternative foundation in community development that is not only oriented towards economic growth but also towards achieving blessings and balance in life in accordance with the principles of maqashid sharia.